The Role of Mineral Composition on the Frictional and Stability Properties of Powdered Reservoir Rocks. Issue 2 (27th February 2019) - Zhang, Fengshou; An, Mengke; Zhang, Lianyang; Fang, Yi; Elsworth, Derek
Abstract: The growing hazard of induced seismicity driven by the boom in unconventional resources exploitation is strongly linked to fault activation. We perform laboratory measurements on simulated fault gouges comprising powdered reservoir rocks from major oil and gas production sites in China, to probe the control of mineral composition on fault friction and stability responses during reservoir stimulation. Double direct shear experiments were conducted on gouges with phyllosilicate content ranging from 0 to 30 wt.% and grain sizes <150 μm, at constant normal stresses of 10–40 MPa and conditions of room temperature and water saturation. The velocity step and slide‐hold‐slide sequences were employed to evaluate frictional stability and static healing, respectively. Results indicate that the mineralogy of the gouges exhibit a strong control on the frictional strength, stability, and healing. Phyllosilicate‐rich samples show lower frictional strength μ and higher values of ( a − b ), promoting stable sliding. For the gouges studied, the frictional strength decreases monotonically with increasing phyllosilicate content, and a transition from velocity weakening to velocity strengthening behavior is evident at 15 wt.% phyllosilicates. Intermediate healing rates are common in gouges with higher content of phyllosilicates, with high healing rates predominantly in phyllosilicate‐poor gouges. As an indispensable component in reservoir rocks, the carbonates are shown to affect both the frictional stability and healing response. These findings can have important implications for understanding the effects of mineralogy on fault behavior and induced seismic potential in geoengineering activities, particularly in reservoirs in China. Key Points: Frictional strength and stability of powdered gouges are affected by the relative amount of tectosilicates, phyllosilicates, and carbonates Gouges with less phyllosilicates exhibit higher healing rates The presence of carbonates can affect gouge frictional stability and healing